Vesicular Dysfunction and the Pathogenesis of Parkinson’s Disease: Clues From Genetic Studies - Ebanks, Kirsten; Lewis, Patrick A.; Bandopadhyay, Rina (Frontiers in Neuroscience, 2020)
Parkinson’s disease (PD) is a common age-related neurodegenerative disorder with disabling motor symptoms and no available disease modifying treatment. The majority of the PD cases are of unknown aetiology, with both genetics and environment playing important roles. Over the past 25 years, however, genetic analysis of patients with familial history of Parkinson’s and, latterly, genome wide association studies (GWAS) have provided significant advances in our understanding of the causes of the disease. These genetic insights have uncovered pathways that are affected in both genetic and sporadic forms of PD. These pathways involve oxidative stress, abnormal protein homeostasis, mitochondrial dysfunction, and lysosomal defects. In addition, newly identified PD genes and GWAS nominated genes point towards synaptic changes involving vesicles. This review will highlight the genes that contribute PD risk relating to intracellular vesicle trafficking and their functional consequences. There is still much to investigate on this newly identified and converging pathway of vesicular dynamics and PD, which will aid in better understanding and suggest novel therapeutic strategies for PD patients.